2008
DOI: 10.1038/nmeth.1216
|View full text |Cite
|
Sign up to set email alerts
|

Efficient targeted transcript discovery via array-based normalization of RACE libraries

Abstract: RACE (Rapid Amplification of cDNA Ends) is a widely used approach for transcript identification. Random clone selection from the RACE mixture, however, is an ineffective sampling strategy if the dynamic range of transcript abundances is large. Here, we describe a strategy that uses array hybridization to improve sampling efficiency of human transcripts. The products of the RACE reaction are hybridized onto tiling arrays, and the exons detected are used to delineate a series of RT-PCR reactions, through which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 24 publications
4
47
0
Order By: Relevance
“…We validated 72% of the assessed model confirming that they are bona fide transcribed units missing from the current annotations. Together these observations support the notion that the human genome is pervasively transcribed as suggested by multiple authors (Kapranov et al 2002;Denoeud et al 2007; The ENCODE Project Consortium 2007; Djebali et al 2008Djebali et al , 2012bClark et al 2011). Further studies are warranted to identify the molecular roles of the new genes identified by RNA-seq (and validated by RT-PCR-seq) and the novel exons of known genes pinpointed by RT-PCR-seq.…”
Section: Wwwgenomeorgsupporting
confidence: 73%
“…We validated 72% of the assessed model confirming that they are bona fide transcribed units missing from the current annotations. Together these observations support the notion that the human genome is pervasively transcribed as suggested by multiple authors (Kapranov et al 2002;Denoeud et al 2007; The ENCODE Project Consortium 2007; Djebali et al 2008Djebali et al , 2012bClark et al 2011). Further studies are warranted to identify the molecular roles of the new genes identified by RNA-seq (and validated by RT-PCR-seq) and the novel exons of known genes pinpointed by RT-PCR-seq.…”
Section: Wwwgenomeorgsupporting
confidence: 73%
“…A systematic analysis of the location of the 59 termini of coding genes expressed in various cell lines was initiated as part of the ENCODE pilot project ( Denoeud et al 2007; The ENCODE Project Consortium 2007; Tress et al 2007;Djebali et al 2008). This project discovered that gene boundaries extend well beyond the annotated termini in 65% of cases, often extending into neighboring genes, leading to the production of chimeric RNAs (Gingeras 2009).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…This project discovered that gene boundaries extend well beyond the annotated termini in 65% of cases, often extending into neighboring genes, leading to the production of chimeric RNAs (Gingeras 2009). A more recent revision of this analysis focusing on chromosomes 21 and 22 revealed additional cases of chimeric transcripts not only connecting neighboring genes but, rather, encompassing distal genes (Djebali et al 2008(Djebali et al , 2012. Characterization of these chimeric transcripts has highlighted that the information stored in the genome and expressed in the transcriptome is not as linear as previously believed Gingeras 2009).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…This approach revealed that most genes do not possess a single TSS, but instead exhibit sets of closely spaced TSSs that will be referred to as Transcription start regions (TSRs) in the following. While the largest number of TSS profiling studies have been performed in mammalian (i.e., human and mouse) systems [Djebali et al 2008; FANTOM Consortium and the RIKEN PMI and CLST (DGT) 2014], CAGE has also been performed in nonmammalian metazoans, including fruit fly (Hoskins et al 2011), nematode (Nepal et al 2013), and zebrafish (Haberle et al 2014). Overall, these studies indicate that the majority of core promoters in metazoan genomes lack TATA elements (Lenhard et al 2012), an unanticipated finding given previously established models of transcription initiation.…”
mentioning
confidence: 99%